2020
DOI: 10.1001/jamanetworkopen.2020.28557
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Benzodiazepine Use With or Without Opioid Use and All-Cause Mortality in the United States, 1999-2015

Abstract: Key Points Question Is benzodiazepine use, with or without opioid use, an independent risk factor for all-cause mortality or a marker for underlying conditions associated with death? Findings In this cohort study of 5212 individuals from a large, nationally representative data set, it was found that benzodiazepine use, with or without opioid use, was associated with a doubling in all-cause mortality risk in comparison with the use of low-risk antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 38 publications
1
41
0
1
Order By: Relevance
“…Although this approach may be effective for managing anxiety, it is also associated with significant risks of fatal and nonfatal overdoses. 8,[61][62][63] To optimize safety, alternative approaches to treating anxiety and depression-pharmacological or nonpharmacological-should be considered when opioids are also prescribed. The coprescribing of benzodiazepines and opioids, when deemed appropriate, should be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach may be effective for managing anxiety, it is also associated with significant risks of fatal and nonfatal overdoses. 8,[61][62][63] To optimize safety, alternative approaches to treating anxiety and depression-pharmacological or nonpharmacological-should be considered when opioids are also prescribed. The coprescribing of benzodiazepines and opioids, when deemed appropriate, should be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 70.9% of new persistent opioid users lled a sedative-hypnotic prescription during the study period as well, while 98.2% of new persistent sedativehypnotic users lled an opioid prescription. Sedative-hypnotics are known to potentiate the respiratory depressive effects of opioids [33], and concomitant opioid and sedative-hypnotic use has been associated with increased rates of long-term opioid use, opioid overdose and all-cause mortality [34][35][36][37]. In particular, pre-operative sedative-hypnotic use among opioid-naïve patients increases the risk of long-term opioid use post-operatively [38].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that patients in plans with PA were much less likely to be co-prescribed benzodiazepines may reflect algorithms to identify co-prescribing of benzodiazepines and buprenorphine-naloxone and programs to reduce such co-prescribing [20]. Co-prescribing of opioids with benzodiazepines is associated with a higher mortality risk [21,22]. The label for buprenorphine-naloxone (brand name Suboxone) states that prescribers should '[u]se caution in prescribing SUBOXONE sublingual tablet for patients receiving benzodiazepines or other CNS depressants and warn patients against concomitant selfadministration/misuse'.…”
Section: Discussionmentioning
confidence: 99%